How Store Distributors Create Customer Value (Survey of Local Fashion Consumers in Bandung) - Taufik Zulfikar; Ine Aprianti; Eva Rachmawati; Rika Kartika (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Different marketing methods from store distributors (distros) to sell clothing (clothing) are exciting to use as research themes. This study aims to analyze the influence of social media and supply chain on customer value impact on brand equity. The sample in this study is consumers (end-users) from distributions in the city of Bandung. The research method is quantitative research with an analysis method using path analysis. The study results show that there is a partial or simultaneous influence of social media and supply chain on customer value which has implications for brand equity.